2020
DOI: 10.1039/d0em00222d
|View full text |Cite
|
Sign up to set email alerts
|

Tris(2-chloroethyl) phosphate, a pervasive flame retardant: critical perspective on its emissions into the environment and human toxicity

Abstract: Regulatory and manufacturers’ voluntary activities led to a market shift in the use of flame retardants (FRs). Organophosphate ester flame retardants (OPFRs) have emerged as a replacement to polybrominated diphenyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 140 publications
0
7
0
1
Order By: Relevance
“…183,184 Deplorably, tris(2-chloroethyl) phosphate (TCEP), a pervasive flame retardant (FR), is ubiquitous in a range of consumer products such as plasticizers, preservatives, and fragrances. 23 Due to the high volatilization propensity of TCEP (volatilization flux of 1100 ng m −3 day −1 ), it can leach easily from the consumer products and get released into the environment. 184 Therefore, TCEP is one of the widespread pollutants in the soil environments.…”
Section: Novel Flame Retardants (Frs)mentioning
confidence: 99%
See 1 more Smart Citation
“…183,184 Deplorably, tris(2-chloroethyl) phosphate (TCEP), a pervasive flame retardant (FR), is ubiquitous in a range of consumer products such as plasticizers, preservatives, and fragrances. 23 Due to the high volatilization propensity of TCEP (volatilization flux of 1100 ng m −3 day −1 ), it can leach easily from the consumer products and get released into the environment. 184 Therefore, TCEP is one of the widespread pollutants in the soil environments.…”
Section: Novel Flame Retardants (Frs)mentioning
confidence: 99%
“…TCEP can easily reach the soil through biotic and abiotic factors, exhibit phytoaccumulation, and threaten the food chain by accumulating in edible crops (). 23,203–205 Hence, policies and regulations on the levels of OPEs should be effective, especially for agricultural lands.…”
Section: Novel Flame Retardants (Frs)mentioning
confidence: 99%
“…167 The available meta-analysis dada confirmed that tris (2-chloroethyl) phosphate (TCEP), a pervasive FR, is carcinogenic in humans. 168 An ex vivo human placental perfusion model confirmed the maternal–foetal transfer of bisphenols. 36…”
Section: Potential Human Health Risks Of Cecsmentioning
confidence: 87%
“…As the presence of leached antimony in bottled water is a serious public health and safety concern, a detailed analysis of the published data on the presence, concentration, and leaching of PET is essential [38]. The persistence and toxicity risk aspects of PET additives are summarized in Table 2 [39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Synthetic Plastics-categories and Petmentioning
confidence: 99%